EKSTENSION FUNNEL DAN FUNNEL STAND UNTUK MEMPERMUDAH MEMASUKKAN CAIRAN ASPAL KE PICNOMETER 50 ML GUNA MENGUKUR MASSA JENIS ASPAL - Adi Wiyono (Politeknik Negeri Malang, 2020)
Abstract - Picnometer is a tool made of glass that has a shape that resembles a perfume bottle. Picnometer is a tool used to measure density or fluid density. There are various sizes of picnometer, but what is often used in the laboratory is the size of 50 ml. Constraints that often occur when measuring density are measurements that cannot run optimally and result in specific gravity taking takes longer. The reason is when moving the asphalt liquid to an asphalt liquid picnometer about the neck of the picnometer, so that repetitive displacement is carried out. When measuring material density, the asphalt temperature ranges from 150 ° C - 170 ° C. Here a PLP (Education Laboratory Staff) of Malang State Polytechnic makes an improvement on the asphalt liquid density. Modifying asphalt density measuring aids, namely funnel extension (funnel) and funnel stand. With the modification, it is hoped that the density measuring instrument can function optimally and become an international standard laboratory